2007
DOI: 10.4039/n06-008
|View full text |Cite
|
Sign up to set email alerts
|

The weevils (Coleoptera: Curculionoidea) of the Maritime Provinces of Canada, I: New records from New Brunswick

Abstract: Seventy-seven species of weevils are newly reported in New Brunswick, increasing the known provincial fauna to 206 species. Trichapion nigrum (Herbst), Ceutorhynchus semirufus LeConte, and Listronotus laramiensis (Angell) are recorded for the first time in Canada. Three species, Bagous planatus LeConte, Plocamus hispidulus LeConte, and Dryocoetes granicollis (LeConte), are removed from the province's faunal list. Components of the fauna are discussed with a particular focus on the introduced species found in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 21 publications
0
28
0
Order By: Relevance
“…Majka et al (2007) reported this species from several sites in the province, where it is often found on Iris versicolor L. This species should therefore be included on the faunal list of NB.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Majka et al (2007) reported this species from several sites in the province, where it is often found on Iris versicolor L. This species should therefore be included on the faunal list of NB.…”
Section: Resultsmentioning
confidence: 98%
“…Polydrusus impressifrons Gyllenhal was newly reported from NB by Majka et al (2007), based on records from Charters Settlement and Moncton (in the University of Moncton Insect Collection). The specimens from Charters Settlement were misidentified and are Polydrusus cervinus (Linnaeus); however, the specimen from Moncton was correctly determined and is Polydrusus impressifrons , and the species remains on the provincial list.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional distribution records were compiled from the following publications: Blackman 1922, 1934; Doane et al 1936; Edson 1967; Bright and Stark 1973; Bright 1976; Furniss and Carolin 1977; Furniss and Johnson 1987; Gast et al 1989; Wood and Bright 1992; Cibrián Tovar et al 1995; Furniss and Johnson 2002; Furniss et al 2002; Lee et al 2006; Majka et al 2007a,b; Humble et al 2010; Smith and Cognato 2010a; Furniss and Kegley 2011; Lee et al 2011). Plant nomenclature was verified using the Missouri Botanical Garden’s Tropicos database (www.tropicos.org).…”
Section: Methodsmentioning
confidence: 99%
“…However, only 1,095 of these Coleoptera specimens were still present in the New Brunswick Museum (NBM) holdings in 2010, many apparently were either sent to other people or were lost to insect pests (Fairweather and McAlpine 2011). Among these specimens are the first occurrences of a number of adventive species to the Maritime provinces: Quedius mesomelinus (Marsham) (Staphylinidae) (Majka and Smetana 2007), Attagenus unicolor japonicas Reitter (Dermestidae) (Majka 2007a), Ernobius mollis (Linnaeus) (Ptiliidae) (Majka 2007a), Brachypera zoilus (Scopoli) (Curculionidae) (Majka et al 2007b), and others, including many that were the first records for New Brunswick and the region.…”
mentioning
confidence: 99%